Sistem Pendukung Keputusan Penentuan Jual Atau Beli Portofolio Menggunakan Analisa Teknikal Dan Fundamental - Nurani, Wahitya Fihtra; Widodo, Arifin Puji; Aliffianto, Ahmad Yanu (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2012)
Today, the development of investment on financial assets have been so rapidly in Indonesia, marked by the number of transactions, companies that go-public, investors and other capital market participants continue to grow. Growth prospects in the Indonesian capital market so rapidly that it was encouraged by the interest of foreign investors coming into the Indonesian capital market. With the stock market, investors can invest in many investment choices, in accordance with the courage to take risks where the investors will always maximize the return that is combined with certain risk in any investment decision. In this undergraduate thesis,we built an application that is expected to investors and prospective investors to make decisions to sell or buy stocks. The purpose of this application is to make the determination of decision support systems to sell or buy portfolios using technical and fundamental analysis. Based on Blackbox testing and evaluation of the application user respondents, it was found that the application or system that has been made to and able to give the final result of the decision to find out which portfolio to be bought or sold. Keywords: Decision Support System, Portfolio, Technical Analysis, Fundamental Analysis.